Toniná, una ciudad Maya de Chiapas : vida y muerte en las postrimerías del colapso Maya - Ruiz González, Judith L. (Paris monographs in American archaeology, 2021)
Toniná was a Mayan city, located between two cultural areas near the Chiapas Highlands. It has been widely proposed that the Maya collapse implied the disappearance and depopulation of many cities; this research addresses the survival of Toniná towards the threshold of the Postclassic.